The House of Whispers - Le Queux, William, 1864-1927 (Salt Lake City, UT : Project Gutenberg, 2004)
"The House of Whispers" by William Le Queux is a novel written in the early 20th century. The story unfolds in the haunting setting of Glencardine Castle in Scotland and centers around the lives of Sir Henry Heyburn, a blind baronet with a mysterious past, and his devoted daughter, Gabrielle. As the novel begins, the reader is drawn into the tension of their lives, suffused with familial loyalty, unspoken secrets, and the shadows of political and personal tragedy that threaten their peace. At the start of the book, we meet Sir Henry and Gabrielle as they navigate their complex relationship in the wake of a significant tragedy that left him blind and confined to a life of quiet contemplation. The vibrant and exciting world Gabrielle yearns for is contrasted starkly with her father's somber existence, leading to a poignant exploration of love, duty, and sacrifice. As she attempts to shield her father from her own turbulent emotions and growing fears, Gabrielle$1 (Bs interactions with her stepmother and the enigmatic James Flockart hint at dark undercurrents and potential dangers lurking in their seemingly idyllic life. The opening chapters establish a richly atmospheric narrative that promises intrigue as Gabrielle's conflicting desires and the threats to her family's wellbeing come into focus. (This is an automatically generated summary.)s
Release date is 2004-01-01
E-text prepared by Juliet Sutherland, Annika Feilbach, and Project Gutenberg Distributed Proofreaders
Keywords: Castles -- Fiction; Mystery fiction; Perthshire (Scotland) -- Fiction